Pola Sebaran dan Keterpusatan Fasilitas Pendidikan sebagai Pelayanan Publik di Kota Pontianak - Syaiful Muazir; Lestari; Muhammad Nurhamsyah; Muhammad Ridha Alhamdani; Rudiyono (P4W LPPM IPB, 2022)
In accordance with the objectives of the Pontianak City Spatial Plan, the development orientation is emphasized in the trade and services sector. In terms of essential services, Educational facilities are means to develop human resources. Along with population growth, Educational facilities and their distribution need to be improved. This article aims to examine the distribution and centralization of Educational facilities as an evaluation for the arrangement of the distribution of services. Besides, it can be a case study for other cities in managing the distribution of facilities. The distribution of access and Educational facilities is assessed through network analysis consisting of calculations of degree, closeness, betweenness, and eigenvector. From the results obtained, South Pontianak District and East Pontianak District are the areas with the highest or largest scores, especially in measuring closeness, betweenness, and eigenvector. It is indicated that the two districts tend to be the most central areas. Meanwhile, for the superimposition between access and distribution of facilities, it is found that Higher Education facilities tend to be facilities with a